Design and Implementation of a Highly Reliable Anti-Collision Mechanism for CPCI Backboard Communication System - LU Qi; ZHOU Xuexun; JIANG Guotao (机车电传动)
A highly reliable and anti-collision mechanism for data communication between master and slave control modules was proposed, and corresponding functional modules on the FPGA were realized, which integrated the CPCI backboard communication and DPRAM technologies as well as cooperated with CPU software , so as to implement the anti-collision data transmission between master and slave control modules. This mechanism could promote the accuracy and reliability of the system communication effectively.